Times of Insight: Conscience, Corporations, and the Common Good - Goodpaster, Kenneth E. (Issues in Business Ethics; Eminent Voices in Business Ethics, 2022)
This open access book traces the research and teaching contributions of Kenneth Goodpaster over more than 45 years of his career. The book shows the content and the progression of these themes over the years identifying four insights in applied ethics: the moral insight, the institutional insight, the anthropological insight, and the Socratic insight. It highlights such concepts as conscience, corporate responsibility, corporations as agents and as recipients, stockholders, stakeholders, comprehensive moral thinking, and ethics education. In addition, Goodpaster explains phrases such as teleopathy, moral projection, human dignity, and the common good. Finally, the book examines with concern the implications of the foregoing for the polarizing and partisan trends in contemporary business behavior. Kenneth Goodpaster's new book, Times of Insight: Conscience, Corporations, and the Common Good reflects the culmination of 50 years of incredible philosophical insights forming the basis of business ethics. His concept of 'corporate conscience' as a moral projection from individual conscience to organizational behavior is both an original as well as a most worthwhile approach to organizational responsibility. Coupling that with a clear notion of the common good, Goodpaster provides substantive grounds for a creative analysis of ethical issues in business. This is one of the most exciting new books in the field. - Patricia H. Werhane, Professor Emerita, University of Virginia and Professor Emerita, DePaul University. "Beginners beware. "Wickedly interdisciplinary" describes corporate ethics. More than "interdisciplinary," the field asks questions that range across disciplines, nations and centuries. Who better to cut this Gordian Knot than Ken Goodpaster, a true giant in the field, who mixes a prodigious knowledge of contemporary corporations with a deep understanding of intellectual history to produce a new and stunning amalgam. A must-read." - Thomas Donaldson, The Mark O. Winkelman Professor, The Wharton School, University of Pennsylvania As one of the pioneers in business ethics, Kenneth Goodpaster has given us a great gift of synthesizing 50 years of philosophical reflection and corporate practice on some of the most important questions and issues for business today. This work is not nostalgia, but an important source of wisdom for leaders today and into the future. - Dr. Michael Naughton, Director, Center for Catholic Studies, Koch Chair in Catholic Studies, University of St. Thomas